Existence of solutions of strongly nonlinear elliptic equations in Rn - Benkirane, A.; Kbiri Alaoui, M. (Revista Matemática Complutense, 2001)
The paper is dedicated to the existence of local solutions of strongly nonlinear equations in RN and the Orlicz spaces framework is used.